2020
DOI: 10.1107/s2056989020005848
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, crystal structure and Hirshfeld surface analysis of N-(4-chlorophenyl)-5-cyclopropyl-1-(4-methoxyphenyl)-1H-1,2,3-triazole-4-carboxamide

Abstract: The title compound, C19H17ClN4O2, was obtained via a two-step synthesis involving the enol-mediated click Dimroth reaction of 4-azidoanisole with methyl 3-cyclopropyl-3-oxopropanoate leading to the 5-cyclopropyl-1-(4-methoxyphenyl)-1H-1,2,3-triazole-4-carboxylic acid and subsequent acid amidation with 4-chloroaniline by 1,1′-carbonyldiimidazole (CDI). It crystallizes in space group P21/n, with one molecule in the asymmetric unit. In the extended structure, two molecules arranged in a near coplanar fashion rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…A similar location of the cyclopropyl ring relative to the 1,2,3-triazole ring was also observed in 5-cyclopropyl-1-(3methoxyphenyl)-1H-1,2,3-triazole-4-carboxylic acid (Pokhodylo et al, 2017), but in the structure of the related compound N-(4-chlorophenyl)-5-cyclopropyl-1-(4-methoxyphenyl)-1H-1,2,3-triazole-4-carboxamide (Pokhodylo & Slyvka et al, 2020), the cyclopropyl ring is close to coplanar with the aryl substituent. An intramolecular N4-H4Á Á ÁN3 close contact (HÁ Á ÁN = 2.37 Å ; N-HÁ Á ÁN = 106 ) is observed.…”
Section: Structural Commentarysupporting
confidence: 66%
See 2 more Smart Citations
“…A similar location of the cyclopropyl ring relative to the 1,2,3-triazole ring was also observed in 5-cyclopropyl-1-(3methoxyphenyl)-1H-1,2,3-triazole-4-carboxylic acid (Pokhodylo et al, 2017), but in the structure of the related compound N-(4-chlorophenyl)-5-cyclopropyl-1-(4-methoxyphenyl)-1H-1,2,3-triazole-4-carboxamide (Pokhodylo & Slyvka et al, 2020), the cyclopropyl ring is close to coplanar with the aryl substituent. An intramolecular N4-H4Á Á ÁN3 close contact (HÁ Á ÁN = 2.37 Å ; N-HÁ Á ÁN = 106 ) is observed.…”
Section: Structural Commentarysupporting
confidence: 66%
“…In our previous studies, new active compounds with a 1,2,3triazolyl-4-carboxamide motif were reported (Shyyka et al, 2019;Pokhodylo, Shyyka, Finiuk & Stoika, 2020;Pokhodylo, Slyvka & Pavlyuk, 2020). Additionally, 1,2,3-triazolyl-4carboxamide derivatives were found to be inhibitors of the Wnt/-catenin signalling pathway (Obianom et al, 2019).…”
Section: Chemical Contextmentioning
confidence: 96%
See 1 more Smart Citation